THE EFFECT OF BRAND IMAGE AND PRODUCT QUALITY ON PURCHASING DECISIONS OF NEW ERA BRAND SHOE PRODUCTS - Hamyat, Hasby; ., Suharlian; ., Sutini (Fakultas Ekonomi Dan Bisnis Universitas Sulawesi Tenggara, 2020)
This study aims to determine the effect of brand image and product quality on product purchasing decisions for New Era brand shoes (Study at the Mandonga Blessing Shoe Shop). The sample in this study were 30 respondents who were taken accidentally who had used and bought New Era brand shoes. This study uses multiple linear regression analysis tools.The study results found that simultaneously brand image and product quality had a positive and significant effect on purchasing decisions. Partially, brand image and product quality have positive and significant influence on purchasing decisions.